Estimating Tourists’ Willingness to Pay for Conservation of Natural Resources in Thailand: Evidence from Khao Laem Ya-Mu Ko Samet National Park - May Myat Noe; Nophea Sasaki; Malay Pramanik; Issei Abe; Takuji W. Tsusaka (Tourism and Hospitality)
Understanding the economic value of natural resources is essential for the sustainable management of national parks. However, most existing studies focus on single conservation objectives and overlook the valuation of multiple resources within the same ecosystem. This study estimates tourists’ willingness to pay (WTP) for the conservation of four natural resources—crab-eating macaques, coral reefs, dry evergreen forests, and clean air—within Khao Laem Ya-Mu Ko Samet National Park in Thailand. Using the contingent valuation method and seemingly unrelated regression (SUR) analysis, data were collected from 205 tourists using structured surveys. The results show that dry evergreen forests received the highest average WTP (THB 129/year), followed by coral reefs (THB 125), clean air (THB 110), and crab-eating macaques (THB 107). At the population level, aggregate annual WTP values ranged from THB 85.7 million to THB 103.2 million across the resources. Age and awareness levels were consistent positive predictors of WTP, while other influencing factors—such as education, income, nationality, and residential location—varied by resource type. The findings provide empirical insights for designing resource-specific conservation strategies and highlight the potential of economic valuation to support sustainable financing mechanisms and policy development for protected area management.